Media Representation of Infanticide by the Father and Demands for the Necessity of Reviewing the Legal Sentence - Leila Rahnama (پژوهشهای حقوقی)
The punishment for the intentional murder of a child by the father in accordance with the Islamic Penal Code of Iran is receiving blood money and ta'zir (Discretionary Punishment). In Islamic jurisprudence, the sentence of prohibition of fathers' retribution has adherents and opponents. The legislator trends to the adherents and has recognized the mentioned sentence. The legislator has announced that one of the conditions in related to Revenge (Avenge for Blood), is discarded of the paternity between the child and father. The mentioned rule has always been challenged and criticized by criminal lawyers and so far they have not succeeded in changing the will and opinion of the legislator in this regard. Due to the proliferation of mass media, public opinion is strongly influenced by media representations of father-child killing, and such crimes are often reported by the media. People's awareness of the non-retribution of the father through the media has consequences that create the need to reconsider. It seems that it is possible to reconsider and modify the legal rule prohibiting in relation of the father in case of intentional killing the child and to persuade the legislator to change and modify it with the help of experts in jurisprudence. This research has been done by descriptive-analytical method based on library resources and news databases.